Effects of Evosure on Nursery Pig Performance - H. Williams; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 360 pigs (PIC C-29 × 359, initially 13.1 lb BW) were used in a 42-d growth trial evaluating the effects of Evosure on nursery pig performance. Evosure is a yeastbased technology designed to enhance weaned pig performance. Pigs were weaned at approximately 16 to 20 d and allotted to pens based on initial BW and gender in a completely randomized design. The 3 dietary treatments included a control diet, or the control diet with Evosure (NUTRIQUEST, Inc., Mason City, IA) fed at 1.0 lb/ton fed from d 0 to 21 followed by 0.5 lb/ton fed from d 21 to 42, or 1.0 lb/ton fed from d 0 to 42. Experimental diets were fed in 3 phases (Phase 1, d 0 to 7; Phase 2, d 7 to 21; and Phase 3, d 21 to 42 post-weaning) and in meal form. Overall (d 0 to 42), no differences in growth performance or final BW were observed among dietary treatments. In conclusion, under these experimental conditions, added Evosure, regardless of level, did not impact nursery pig performance.
Keywords: Evosure; feed additive; growth performance; nursery pig